Assessment of quantitative polymerase chain reaction for equine herpesvirus‐5 in blood, nasal secretions and bronchoalveolar lavage fluid for the laboratory diagnosis of equine multinodular pulmonary fibrosis. (18th January 2016) - Pusterla, N.; Magdesian, K. G.; Mapes, S. M.; Zavodovskaya, R.; Kass, P. H.
Summary: Reasons for performing study: The ante mortem diagnosis of equine multinodular pulmonary fibrosis (EMPF) relies on histopathological results and polymerase chain reaction (PCR)‐positive equine herpesvirus (EHV)‐5 testing of lung tissue. Polymerase chain reaction detection of EHV‐5 in bronchoalveolar lavage fluid (BALF) is commonly used to support a diagnosis of EMPF. However, the diagnostic power of EHV‐5 testing on BALF and other biological samples such as blood and nasal secretions has yet to be shown to support a diagnosis of EMPF. Objectives: To determine the frequency of detection and the viral loads of EHV‐5 by quantitative PCR (qPCR) in blood, nasal secretions and BALF from horses confirmed with EMPF, healthy horses and horses with non‐EMPF pulmonary diseases. Study design: Prospective study. Methods: The study population consisted of 70 adult horses divided into 4 groups based on a combination of clinical findings, cytology of BALF, imaging studies of the thoracic cavity and histopathology of pulmonary tissue: control group (n = 14), EMPF group (n = 11); inflammatory airway disease group (n = 32); and non‐EMPF interstitial lung disease group (n = 13). For each horse, whole blood, nasal secretions and BALF were available for EHV‐5 qPCR testing. Sensitivities, specificities and their respective 95% confidence intervals were calculated for viral loads from blood, nasal secretions and BALF. In addition, these measures were calculated for combined use of blood and nasal secretions. Results: The detection of EHV‐5 in BALF was strongly associated with EMPF (sensitivity 91%, specificity 98.3%). Detection of EHV‐5 in blood was, independent of the viral loads, strongly associated with EMPF with a sensitivity of 91% and specificity of 83.1%. The detection of EHV‐5 in nasal secretions displayed the highest sensitivity (72.7%) and specificity (83.1%) at a level of >245, 890 glycoprotein B target genes/million cells to support a diagnosis of EMPF. Dually positive blood and nasal secretions at any viral loads in support of EMPF yielded a sensitivity and specificity of 90% and 89.8%, respectively. Conclusions: Although histopathological confirmation (lung biopsy) is considered the gold standard for EMPF diagnosis, results of qPCR testing of BALF or a combination of whole blood and nasal secretions should be regarded as clinically useful in support of this diagnosis. The latter testing may be relevant when dealing with horses in respiratory distress, for which invasive procedures such as BALF collection or lung biopsies may be detrimental to their health.